MINIMALLY INVASIVE SURGICAL METHOD FOR FRACTURES OF THE PROXIMAL HUMERUS (Journal of Universal Science Research, 2023)
Purpose of work was improving treatment outcomes by developing an extramedullary minimally invasive method in fractures of the proximal portion of the humerus.